Evaluate the Freeway Space and Velocity of Closure of Mandible in FMR Patients Pre and Post Temporisation - Kumar, Lakshay; Venugopalan, Suresh (Journal of Neonatal Surgery, 2025)
Objective: This clinical study aimed to evaluate changes in freeway space and mandibular closure velocity in patients undergoing full mouth rehabilitation (FMR), before and after the placement of temporisation crowns. Methods: A total of 25 systematically healthy patients requiring tooth-supported FMR were enrolled. Using a mechanical jaw tracker and computerized mandibular scanner, vertical dimension at rest (VDR), vertical dimension at occlusion (VDO), and mandibular movement velocities were recorded pre- and post-temporisation. Temporisation was performed using Poly Methyl Methacrylate crowns. Freeway space was calculated as the difference between VDR and VDO. Paired t-tests were used to analyze pre- and post-treatment differences. Results: Post-temporisation, a significant increase in VDO was observed (p = 0.003), while VDR showed a non-significant increase (p = 0.07). Consequently, freeway space significantly decreased (p = 0.005), indicating improved occlusal balance. No significant change was noted in mandibular opening velocity (p = 0.058), but closure velocity significantly increased after temporisation (p = 0.031), suggesting enhanced neuromuscular coordination during occlusion. Conclusion: Temporisation in FMR patients leads to significant improvement in occlusal vertical dimension and closure velocity, with a notable reduction in freeway space. These findings underscore the clinical value of temporisation in reestablishing occlusal harmony and optimizing mandibular function during the rehabilitative phase of treatment.